Osteoblastic and cytokine gene expression of implant‐adherent cells in humans. Issue 1 (11th October 2012) - Bryington, Matthew; Mendonça, Gustavo; Nares, Salvador; Cooper, Lyndon F.
Abstract Objectives Implant surface topography is a key determinant affecting osteoblastic differentiation and cell–cell signaling of implant‐adherent cells. Materials and methods To assess the early osteoinductive and cell–cell signaling events in adherent cells, commercially pure titanium implants (2.2 × 5 mm) with nanotopography (HF‐treated TiO2 grit‐blasted) were compared with micron‐scale topography TiO2 grit‐blasted (micron‐scale, control) implants in vivo. Six implants (n = 3/surface) were placed in 10 systemically healthy subjects and removed by reverse threading at 1, 3, and 7 days. Gene expression profiles of adherent cells were interrogated using low‐density RT‐PCR arrays. Results Osteoinduction was not observed at day 1 on either surface. At 3 days, elevated levels of BMP6, osteopontin, and osterix (OSX) were observed in RNA of cells adherent to both micron‐scale and nanotopography surfaces. Both surfaces supported osteoinductive gene expression at 7 days; however, modest elevations of most mRNAs and significantly higher OSX mRNA levels were measured for cells adhered to nanotopography implants. Further, chemokine and cytokine profiles including CXCL10, CXCL14, IL‐9, IL‐22, and TOLLIP were upregulated on nanotopographic surfaces as compared with microtopographic surfaces. Conclusions Implants with superimposed nanoscale topography generate a greater induction of genes linked to osteogenesis and cell–cell signaling during the early phases of osseointegration.